(untitled) (Global Journal of Management and Business Research, 2019)
Despite the increased presence of women in the labor market and their presence in companies, their representation in executive management positions remains even lower. This study aims to understand the obstacles perceived by women executives who hinder their progress towards management positions and the means to implement to allow a better representation of women in management positions. We conducted qualitative exploratory research with a sample of women executives from private companies in Cameroon. The results of our analyzes have thus concluded that women face both socio-organizational and individual barriers that limit their access to management positions. At the individual level we noted the lack of professional ambition and the lack of support of the spouse and at the socio-organizational level, the work-family conflict, the differential treatment between men and women, the predominance of the masculine gender and the lack of support for career development were noted.